Hollow Threats: Transnational Food and Beverage Companies' Use of International Agreements to Fight Front-of-Pack Nutrition Labeling in Mexico and Beyond - Eric Crosbie; Angela Carriedo; Laura Schmidt (Kerman University of Medical Sciences, 2022)
In October 2019, the Mexican government reformed its General Health Law thus establishing the warning approach to front-of-pack nutrition labeling (FOPNL), and in March 2020, modified its national standard, revamping its ineffective FOPNL, one preemptively developed by industry actors. Implementation is scheduled for later in 2020. However, the new regulation faces fierce opposition from transnational food and beverage companies (TFBCs), including Nestlé, Kellogg, Grupo Bimbo, Coca-Cola, PepsiCo through their trade associations, the National Manufacturers, American Bakers Associations, the Confederation of Industrial Chambers of Mexico and ConMéxico. Mexico, as a regional leader, could tip momentum in favor of FOPNL diffusion across Latin America. But the fate of the Mexican FOPNL and the region currently lies in this government's response to three threats of legal challenges by TFBCs, citing international laws and guidelines including the World Trade Organization (WTO), Codex Alimentarius, and the North American Free Trade Agreement (NAFTA)/US-Mexico-Canada Agreement (USMCA). In this perspective, we argue that these threats should not prevent Mexico or other countries from implementing evidence-informed policies, such as FOPNLs, that pursue legitimate public health objectives.